Evolution of global airline strategic alliance and consolidation in the twenty-first century - FAN, Terence P. C. (Institutional Knowledge at Singapore Management University, 2001)
Global airline strategic alliances have emerged since the late 1980s, and their number has slowly risen through the years. Will the number of such alliances continue to proliferate? Or will airlines consolidate with one another to form mega-carriers? In this paper, the likelihood of various airline consolidation and alliance development possibilities was examined based on a number of high-level trends and forces. The most probable near-term industry alliance and consolidation structure is described, accompanied with a probable path of evolution. These predictions have important implications for managers of strategic alliances, carriers who are currently in an alliance as well as carriers who are planning to join one